Avaliação da erosão hídrica por meio da Equação Universal de Perda de Solo Modificada (MEUPS) na bacia hidrográfica do Ribeirão Jacutinga, Rio Claro (SP) - Oliveira, Mariana Morila [UNESP] (2015)
Water erosion is one of the main processes responsible for soil degradation, resulting in loss of parcels of land suitable for agriculture, to the loss of agricultural inputs and the resulting drift of pesticides and excess sediment to rivers, causing phenomena such as the siltation and eutrophication of water bodies. Such a scenario makes it necessary to perform work of a technical and scientific to provide subsidies to land-use planning, in order to protect natural resources biotic and abiotic. To develop this work is necessary to find a unit of analysis capable of integrating the different elements of the landscape, hydrosphere, atmosphere, biosphere and lithosphere. Therefore we adopt for this work the watershed as main unit studies. From this question, this project will focus on the assessment of surface water erosion through MEUPS (Equation Modified Universal Soil Loss) predictive model. With the aid of maps, remote sensing products, and the use of geotechnology, this study aims to evaluate for the for Natural Erosion Potential the basin of the Jacutinga river, located in Rio Claro - SP